Avaliação de tecnologias fotovoltaicas para integração em automóveis solares - Rodrigues, José Matheus Queiroz (Universidade Federal de São Carlos, 2025)
This work presents a comparative analysis of the main photovoltaic technologies regarding their applicability in solar-powered vehicles, emphasizing energy efficiency, durability, flexibility, raw material availability, ease of production, and end-of-life disposal implications. To this end, a methodology based on six technical criteria and six representative technologies is adopted — crystalline silicon (c-Si), polycrystalline silicon (p-Si), amorphous silicon (a-Si), copper–indium–gallium–selenide (CIGS), cadmium telluride (CdTe), and perovskites — as defined by the author. Each technology was assigned scores ranging from 1 to 5 for each criterion, and the resulting averages enabled a consolidated assessment. The results indicate that crystalline silicon — particularly monocrystalline silicon — exhibits the best balance between efficiency, stability, and industrial maturity, achieving the highest average score among the technologies analyzed. Thin-film technologies such as CIGS and CdTe offer advantages in terms of low weight and high absorption in thin layers, while perovskites stand out for their high efficiency and extreme flexibility, although they are still limited by durability issues and environmental concerns related to end-of-life management. The study concludes that tandem solutions, such as perovskite-on-silicon configurations, represent the most promising route to reconcile efficiency and reliability in solar vehicles, and recommends further efforts in encapsulation, production scale up, and the development of recycling pathways to enable their adoption in the automotive sector.
Evaluation of photovoltaic technologies for integration into solar vehicles
Keywords: Energia solar; Células fotovoltaicas; Carros solares; Perovskita; Silício cristalino; Solar energy; Photovoltaic cells; Solar vehicles; Perovskite; Crystalline silicon; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; 7. Energia limpa e acessível